Forward Problem Solving for Non-Invasive Electrical Resistance Tomography System - Yasmin, Abdul Wahab; Ruzairi, Abdul Rahim; Jaysuman, Pusppanathan; Mohd Hafiz, Fazalul Rahiman; Leow, Pei Ling; Suzanna, Ridzuan Aw; Herlina, Abdul Rahim (Malaysian Society for Computed Tomography and Imaging (MyCT), 2018)
This paper aims to provide a forward problem solving for non-invasive electrical resistance tomography. A finite element model (FEM) using COMSOL Multiphysics is implemented for generating the sensitivity map for ERT system. Later, a masking data for a better sensitivity map was done to optimize the map. As a result, the sensitivity map can be used later for reconstructing the image of the medium of interest.